Characterisation of paraffin-based hybrid rocket fuels loaded with nano-additives - Akhter, Md. Zishan (2020)
In this work, a new composition based on Paraffin wax and HTPB fuel, loaded with nanoparticles has been proposed for hybrid propulsion system. Lithium aluminium hydride (LiAlH4) and Magnesium hydride (MgH2) nanoparticles have been used as additives. A detailed rheological, thermal and ballistic characterisation has been carried out. The Magnesium hydride doped hybrid fuel exhibits lower viscosity as compared to the Lithium aluminium hydride doped one, leading to comparatively enhanced entrainment-aided combustion. LiAlH4 doped hybrid fuels also exhibit solid-like behaviour and thus greater stability in the solid phase in contrast to the MgH2 doped fuel. LiAlH4 doped fuel is thermally more stable and produces relatively greater residual-mass. The loading of nanoparticles significantly improves the fuel regression performance during ballistic firing. This can be attributed to the release of nascent hydrogen and metal nanoparticles during dehydrogenation of metal hydrides. Regression rate enhancement in the range of 350%–475% is observed in comparison to the conventional HTPB hybrid fuels. A power law governing regression rate has been proposed for the tested hybrid fuels.